Characteristics of Budget Law special principles - Ya. O. Ponomarova; M. Yu. Novyk; R. V. Kobko (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The purpose of the article is to define and characterise the principles of Budget Law. It is argued that the principles of budget law are most appropriately understood as the starting points, the initial ideas which form the basis for the functioning and further development of the relevant branch of law. The principles are intended to reflect the basic realities of social life in which certain processes under study take place or social relations are carried out. Thus, not only the functioning of Budget Law, but also all social legal relations regulated by the rules of the legal field under study depend on the content of the principles under study.